2017
DOI: 10.1103/physreva.96.013813
|View full text |Cite
|
Sign up to set email alerts
|

Klein tunneling in driven-dissipative photonic graphene

Abstract: We theoretically investigate Klein tunneling processes in photonic artificial graphene. Klein tunneling is a phenomenon in which a particle with Dirac dispersion going through a potential step shows a characteristic angle-and energy-dependent transmission. We consider a generic photonic system consisting of a honeycomb-shaped array of sites with losses, illuminated by coherent monochromatic light. We show how the transmission and reflection coefficients can be obtained from the steady-state field profile of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Klein tunneling was first envisioned in relativistic quantum physics [42] and experimentally observed in graphene which exhibits pseudospin-1/2 carrier dynamics [1][2][3]. Photonic analog of this 2D material, i.e., the photonic graphene, provides a platform for observing the Klein tunneling in the classical wave system [43,44]. It has also been demonstrated that the "super" Klein tunneling effect, i.e., total transmission for all incident angles, is supported in the photonic pseudospin-1 systems which exhibit Dirac-like cone band dispersions [22], the mechanism of which has also been understood from the concept of "complementary materials" in EM wave theory [22].…”
Section: A Klein Tunnelingmentioning
confidence: 99%
“…Klein tunneling was first envisioned in relativistic quantum physics [42] and experimentally observed in graphene which exhibits pseudospin-1/2 carrier dynamics [1][2][3]. Photonic analog of this 2D material, i.e., the photonic graphene, provides a platform for observing the Klein tunneling in the classical wave system [43,44]. It has also been demonstrated that the "super" Klein tunneling effect, i.e., total transmission for all incident angles, is supported in the photonic pseudospin-1 systems which exhibit Dirac-like cone band dispersions [22], the mechanism of which has also been understood from the concept of "complementary materials" in EM wave theory [22].…”
Section: A Klein Tunnelingmentioning
confidence: 99%
“…Finally, we note the intensive experimental activities in simulating the honeycomb lattices by cold atoms and optical lattices 64 . In particular, the possibility of Klein tunneling in these system has been examined [65][66][67][68][69] and observed recently 70,71 . These simulated graphene systems may provide an alternative platform for observing the perfect transmission at oblique incidence.…”
Section: B Experimental Feasibilitymentioning
confidence: 99%
“…Although the requirement for all the modes to have equal loss rates is a significant restriction, there are many physical systems made of identical elements, for which the losses are expected to be be equal, so the theorem applies. For examples, we can look to photonic lattice structures [18,19], arrays of semiconductor micro cavities with same detuning [20] and continuous systems, like waveguide or waveguide networks with isotropic geometry [21].…”
Section: Conservation Of Gmentioning
confidence: 99%